Screening for chloroform/perchloroethylene-degrading bacterial candidates for bioaugmentation in anaerobic bioprocess and development of chloroform/perchloroethylene-induced toxicity bioassay. - Leng, Amanda Jun Theng. (2013)
Chlorinated organic compounds, such as chloroform (CF) and perchloroethylene (PCE), have negative impact on the environment and human health due to their carcinogenicity. In recent years, anaerobic wastewater treatment processes have garnered increasing interest, but the presence of chlorinated organic compounds in wastewater may adversely affect the efficiency of the microbial consortia within the bioreactors. Bioaugmentation serves as a possible method to reduce the effects of chlorinated compounds through introduction of CF- and PCE-degrading bacteria into the indigenous consortia. Our study aimed at identifying locally-adapted environmental isolates, capable of CF and PCE degradation, as candidates for bioaugmentation. The first aim of this study is to select for strains that may possess either the genetic machinery to degrade CF and PCE and/or tolerance to high CF/PCE concentration. Two screening tests were conducted to fulfill this aim. The first screen involved detection of bacterial strains by PCR using primers directed at genes that were often carried by known dechlorinating-bacteria. The second screen involved culturing the bacteria in the presence of CF/PCE, to observe for tolerance and survival. The second aim is to develop an assay to obtain an indication of CF- or PCE-degrading capabilities of the screened bacterial strains. The screened strains were cultured in known concentrations of CF/PCE and the growth of bacteria was monitored. Any deviation from initial CF/PCE concentration present in the media may be indicative of degradation capability. A new method was developed to estimate the CF/PCE concentration based on the growth profile of CF/PCE-sensitive reference strains when exposed to different CF/PCE concentration. Regression analysis using the growth rate of the reference strains will be used to intrapolate the unknown CF/PCE concentration in the supernatant. Further optimization of the protocol will be needed to accurately assess the bacterial isolates.